Estimates of Tax Revenues from the Arctic Shelf Oil Exploration - KOROSTELYOVA, Victoria Viktorovna; RAZDROKOV, Evgeny Nikolaevich; KRASILNIKOV, Arkady Vladimirovich; MAKAROV, Vladimir Alexandrovich (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
Arctic shelf oil exploration is a capital-intensive and risk-bearing process. The tax concessions are provided in order to facilitate exploration of new oilfields, which would bring additional income to the budgetary system of Russia in the long view. The article provides estimates of tax revenues from the Arctic shelf oil exploration and analysis of impact of the tax concessions on new oilfield exploration in the strategic oil-producing regions of Russia.